L20 Huntington's Disease – Bad For Your Wealth As Well As Your Health?. (17th September 2014) - Rogers, D; Stopford, C; Howard, E; Trender-Gerhard, I; Alusi, S; Davies, R; Craufurd, D
Abstract : Background: The Enroll-HD project aims to recruit one third of the manifest HD patients living in areas served by study sites. We conducted an audit of REGISTRY study participants at two sites (Manchester and Liverpool) to assess the feasibility of this, and to investigate the effect of geographical and socioeconomic factors on equality of access to the service. Aims: To determine the number of REGISTRY participants per 100, 000 of the population in different areas of North West England, and the relationship of this to distance from study sites and indicators of economic deprivation. Methods: The total number of living REGISTRY participants and the number of currently active study participants were calculated for each county and borough in north west England. Postcodes were used to assign subjects to census areas (Lower-layer Super Output Areas; LSOAs) and the distribution of LSOAs containing at least one REGISTRY participant was compared to the overall distribution using the Index of Multiple Deprivations (IMD) of the UK Office of National Statistics. Results: Rates of current REGISTRY participation varied greatly from borough to borough, but was approximately 4/100, 000 across most of the region, rising to 6/100, 000 when inactive participants were included. The borough with the highest rate of participation was the one most geographically distant (about 3 h travel) from the study sites. LSOAs containing a REGISTRY participant were significantly more likely to have a higher IMD score (more deprived). Conclusion: If the prevalence of HD is 12/100, 000, our findings suggest that the goal of recruiting one third of the available subjects is achievable. Distance from the study site does not appear to be a barrier to access in our region. Given that the primary cause of HD is genetic, the significant relationship with indices of deprivation suggests that HD has a detrimental effect on the socioeconomic status of families, as well as the health of affected individuals.